Synthesis, Characterization and Antibacterial Activity of New Derivatives of Imidazolidine having Sulfamethoxazole Moiety - Enas k. Abd alazez; Ayad M.R. Raauf; karima F. Ali (College of Pharmacy / Mustansiriyah University, 2019)
This work includes Synthesis of new series of sulfa drugs derived from sulfamethoxazole containing substituted Imidazolidine moiety.  These compounds expected to have antibacterial activity, due to their Imidazolidine moiety This work includes synthesis of some new Schiff bases (II1-5) by condensation of sulfamethoxazole drug(I) with some aldehydes (1-5) (benzaldehyde, p-chloro benzaldehyde, p-nitro benzaldehyde, p-hyroxy benzaldehyde and p-N, N-dimethyl amino benzaldehyde). These Schiff bases were found to react with glycine, to prepared new imidazolidine derivatives (III1-5). The prepared compounds were characterized by physical properties, FT-IR and of the 1H-NMR spectroscopy. The preliminary study of antibacterial activity of final compounds has considered by well diffusion method. The tested compounds displayed effect against gram negative bacteria:( Acinetobacter species and Pseudomonas aeruginosa) and gram-positive bacteria (Streptococcus pyougenes and Staphylococcus aureus bacteria), which compared to DMSO as control, and good activity compared to sulfamethoxazole as standard.